Role of N-Glycosylation Sites and CXC Motifs in Trafficking of Medicago truncatula Nod Factor Perception Protein to Plasma Membrane - Lefebvre, Benoit (American Society for Biochemistry and Molecular Biology, 2012)
The lysin motif receptor-like kinase, NFP (Nod factor perception), is a key protein in the legume Medicago truncatula for the perception of lipochitooligosaccharidic Nod factors, which are secreted bacterial signals essential for establishing the nitrogen-fixing legume-rhizobia symbiosis. Predicted structural and genetic analyses strongly suggest that NFP is at least part of a Nod factor receptor, but few data are available about this protein. Characterization of a variant encoded by the mutant allele nfp-2 revealed the sensitivity of this protein to the endoplasmic reticulum quality control mechanisms, affecting its trafficking to the plasma membrane. Further analysis revealed that the extensive N-glycosylation of the protein is not essential for biological activity. In the NFP extracellular region, two CXC motifs and two other Cys residues were found to be involved in disulfide bridges, and these are necessary for correct folding and localization of the protein. Analysis of the intracellular region revealed its importance for biological activity but suggests that it does not rely on kinase activity. This work shows that NFP trafficking to the plasma membrane is highly sensitive to regulation in the endoplasmic reticulum and has identified structural features of the protein, particularly disulfide bridges involving CXC motifs in the extracellular region that are required for its biological function.